Potential utilization of filaments and ovules as explant sources in in vitro propagation of Lilium sp. - Budi WINARTO; Suskandari KARTIKANINGRUM; Fitri RACHMAWATI; Dewi PRAMANIK; Herni SHINTIAVIRA; Mega WEGADARA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
Lilies are important cut and pot flowers locally and globally; however, qualified planting materials from in vitro culture are still limited. The culture generally uses scales and leaves, while filaments and ovules are rarely utilized. Filaments and ovules of EXO CF/E, RDF CG/E, and DZ CG/E genotypes of Lilium sp. were explored for their potential to establish in vitro propagation protocol using different Chu N6 medium and their modifications. The 9.9 shoots/explant from 1.5 regenerative explants/replication of RDF CG/E filaments was proven on Chu N6 medium containing 6.79 µM 2,4-dichlorophenoxyacetic acid (2,4-D), 2.27 µM thidiazuron (TDZ), and 90 g L-1 sucrose; 3.3 regenerative explants/replication and 8.4 shoots/explant of EXO CF/E ovules were determined on Chu N6 medium with 2.26 µM 2,4-D, 6.81 µM TDZ and 90 g L-1 sucrose; and slightly improved on Chu N6 macro elements, full vitamins of MS basal medium with 3.39 µM 2,4-D, 3.41 µM TDZ, 150 ml L-1 coconut water (CW) and 60 g L-1 sucrose. The shoots were proliferated on the established media. The shoots of EXO CF/E, RDF CG/E and DZ CG/E genotypes produced varied leaves/shoot, leaf length, leaf width, roots/shoot, root length and bulb diameter on Chu N6 medium hormone free with 1.5% AC, followed by hardening them in a glass house for one month. The hardened-plantlets were acclimatized in plastic pots containing charcoal husk and bamboo compost (1:1) with 39.8-63.6% survivability. The protocol has the potential to be applied to other genotypes or lilies by specific improvements at the acclimatization stage.